Transcriptomic analysis of Sporisorium reilianum in response to the strigolactone analogue GR24 - Seyed SABBAGH; Mahta MAZAHERI; Naser PANJEHKEH; Mohammad SALARI (Phytopathologia Mediterranea, 2012)
A suppression subtractive hybridization (SSH) approach was used to generate cDNA libraries representing genes differentially expressed in the haploid cells of the maize head smut pathogen Sporisorium reilianum exposed to GR24, a strigolactone analogue. Strigolactones are present in root exudates and have been known to trigger germination of parasitic plant seeds and signal mycorrhizal fungi to connect to root systems forming mutualistic relationships. Cell respiration increased within 1 h after GR24 addition, but decreased after 5 and 8 h. All induced cells were used to construct a cDNA library, which contained 1440 clones. The cDNA ESTs were deposited on macro-array membranes and hybridized with P32 cDNA probes obtained from mRNA isolated from S. reilianum yeast cultures exposed or not to 100 nM GR24 for three time intervals. A total of 678 ESTs were identified as differentially expressed during three time-courses in response to GR24. A set of 36 candidate genes were analyzed by qRT-PCR that presented an induction of the genes at 1 h, confirming the hybridization data. Induced genes mostly affect catalysis functions (45%) like cell respiration (27%), and cell signaling (26%). Although the biological significance of this perception remains hypothetical, these results indicate that strigolactones could have a wider biological influence in the rhizosphere than previously recognized.